Strategi Pengelolaan Desa Wisata Untuk Meningkatkan Kunjungan Pelancong Ke Desa Wisata Kreatif Terong Kecamatan Sijuk Kabupaten Belitung - Ingkadijaya, Rahmat; Emansyah, Ferdi; Mariati, Sri (Jurnal Ilmiah Pariwisata, 2022)
This study aims to analyze management strategies for developing and increasing tourist interest in visiting the Terong Creative Tourism Village. This study uses the SWOT analysis method with observations, interviews, documentation, and questionnaires to the Belitung Regency Tourism Office, Terong Village Government, Pokdarwis, the community, and tourists. The results of this study indicate that the main strategy produced is the SO strategy, with the highest score of 3.70 in position I, which has an aggressive growth policy strategy. In implementing this strategy in the future, the Terong Creative Tourism Village must continue to preserve customs and culture, increase tourist attractions, increase tourism promotion by making cultural arts performances and collaborate with MSME artisans so that they can make souvenirs for tourists with sources. Funds and management of Mangrove forests, Aik Deer tourism. Berehun, arrangement of agro-tourism areas, Bukit Tebalu area, culinary tourism, and so on. Keywords: Management Strategy, Tourist Attraction